The Effect of Experimental Methods on Understanding the Use of Science in Elementary Schools - Hamna; Rindiani; Siti Hana; Sulistiyawati (Horizon of Primary Education, 2025)
This study aims to examine the impact of the application of experimental methods on improving the understanding of science concepts in elementary school students. The basis for implementing this study is based on the fact that science learning in elementary schools is still dominated by a theoretical and teacher-centered approach, resulting in students being less actively involved in the learning process. The experimental approach was implemented through a simple activity called "a mini eruption of Mount Merapi," which aims to provide students with direct experience in understanding scientific phenomena. This study used a pretest-posttest design involving eight fourth-grade students of elementary schools 3 Dadakitan as participants. The measurement tool used was a conceptual understanding test administered before and after the experimental activities. The results showed an increase in the average score from 70 in the pretest to 80 in the posttest, indicating an increase in students' understanding of scientific concepts. Furthermore, classroom observations showed that students became more active, enthusiastic, and confident in expressing their ideas during the learning process. These findings indicate that the experimental method not only improves learning outcomes but also fosters students' curiosity, critical thinking, and scientific attitudes. Therefore, the experimental method can serve as an effective learning strategy to strengthen scientific process skills and improve the quality of science learning in elementary schools.